A simple numerical tool to infer whether a species is extinct. Issue 8 (23rd July 2014) - Lee, Tamsin E.; Isaac, Nick
Summary Including uncertain sightings when inferring extinction of a species is relatively new and has proven to be significant. However, including uncertain sightings leads to non‐trivial mathematical problems which are inaccessible to many ecologists. I use the Pohnpei Mountain Starling Aplonis pelzelni to describe an Excel spreadsheet which infers extinction from a sighting record. The spreadsheet implements a Bayesian model which includes uncertainty around the prior, uncertain sightings and survey effort. Survey effort has not been included in extinction models before, but clearly plays a significant role in extinction estimates, which the Pohnpei Mountain Starling example demonstrates. The spreadsheet (included as supplementary material) is user‐friendly, fast and accessible on Windows.